Fabrication of periodic arrays of microholes in thin Ag-films by femtosecond laser pulses - Trang, Nguyen Thi Huyen (Vietnam Journal of Science and Technology, 2017)
Arrays of microholes with different diameters of micro-holes 2, 3, 4 μm and period 6 μm were produced in thin silver films with thicknesses 30, 50, 100, 150 nm by single femtosecond laser pulses with variable pulse energies, focused by different strong focusing optics. The microarray format is used for surface plasmon resonance (SPR) imaging, surface-enhanced IR adsorption (SEIRA) and its potential for applications in multiplex sensing.